Special Features of the Crime’s Subject Under the Article 330 of the Criminal Code of Ukraine (Law and Safety, 2019)
On the basis of the analysis of criminal and legal literature, certain provisions of the Criminal Code of Ukraine and court practice of their application, the author has determined that the description of special features of the crime’s subject through the construction of “in connection with the performance of official duties” used by the legislator in the disposition of the Art. 330 of the Criminal Code of Ukraine indicates the identity of the subject to the category of officials. At the same time, taking into account the dualism of criminal and legal approaches to the definition of the term of “an official” in the descriptions of a victim and the crime’s subject, the author has emphasized on the application of the more narrow concept laid down in Part 3 of the Art. 18 of the Criminal Code of Ukraine and the Resolution of the Plenum of the Supreme Court of Ukraine dated from April 26, 2002 No. 5 “On judicial practice in cases of bribery”.As a result, the author has come to the conclusion that a special subject of the crime under the Art. 330 of the Criminal Code of Ukraine may be officers of the departments of the National Police of Ukraine, the State Investigation Bureau, the Security Service of Ukraine, the Foreign Intelligence Service of Ukraine, the State Border Guard Service of Ukraine, the Office of State Security, the State Fiscal Service of Ukraine, the State Penal Service of Ukraine, the Ministry of Defense of Ukraine, the President of Ukraine, officials of the President’s Administration of Ukraine, Verkhovna Rada of Ukraine, Cabinet of Ministers of Ukraine, National Security and Defense Council of Ukraine, Supreme High Command General Headquarters of Ukraine, the Ministry of Defense of Ukraine, the General Staff of Armed Forces of Ukraine, the unions, military units and units of the Armed Forces of Ukraine, the State Special Transport Service, the State Service for Special Communications and Information Protection of Ukraine, the National Guard of Ukraine, the Council of Ministers of the Autonomous Republic of Crimea, regional, district, city and district in the cities, state administrations and local self-government agencies, as well as officials of enterprises, institutions and organizations that carry out state defense orders, conduct research and perform development in the defense area, etc.
Keywords: corpus delicti; subjects of a crime; special features; an official; performance of official duties; Article 330 of the Criminal Code of Ukraine